Job Autonomy sebagai Moderator pada Pengaruh Job Insecurity terhadap Perilaku Kerja Inovatif - Ardy, Ludi Prasetyo; Fajrianthi, Fajrianthi (Universitas Negeri Surabaya, 2019)
This study aims to examine the role of job insecurity towards innovative work behavior with job autonomy as a moderator. The concept of the three variables were tested using the theoretical concepts of job demand and job control. In the condition of